Retrograde peri-implantitis - Mohamed Jumshad; Shivakumar B; Sudarsan Sabitha; Arun K; Kumar T.S.S (Wolters Kluwer Medknow Publications, 2010)
Retrograde peri-implantitis constitutes an important cause for implant failure. Retrograde peri-implantitis may sometimes prove difficult to identify and hence institution of early treatment may not be possible. This paper presents a report of four cases of (the implant placed developing to) retrograde peri-implantitis. Three of these implants were successfully restored to their fully functional state while one was lost due to extensive damage. The paper highlights the importance of recognizing the etiopathogenic mechanisms, preoperative assessment, and a strong postoperative maintenance protocol to avoid retrograde peri-implant inflammation.